Approaches to alleviating poverty in rural Pakistan - Hussain, Intizar (2004)
More than 12 million people added to the poor in Pakistan between 1993 and 1999. The rising poverty was the result of poor governance and slow economic growth (Asian Development Bank 2002). All available evidence on poverty trends in Pakistan suggests that the problem of poverty in the country worsened during the 1990s, and this was more so in rural areas than in urban areas. Rural economy of the country is caught up in a vicious circle of problems ? rapidly increasing population resulting in decreasing per capita resource base, low literacy level, continued high level of inequity in resource distribution, slow growth in both farm and non-farm sectors, and more importantly, continued poor governance. All these factors adversely affected the efforts to reduce poverty. Agricultural economy, which forms the backbone of broader rural economy of the country, is presently facing three major inter-related problems: (1) increasing water scarcity coupled with continued poor performance of irrigation systems, (2) increasing degradation of land and water resources, and (3) farmers? poor access to other key production inputs and services ? all resulting in actual agricultural productivity levels continuing to be much below the achievable potential levels. Enhancing agricultural productivity through removing these constraints, especially for small farms, is one of the keys to address the problem of food and income poverty. This paper provides an overview of poverty trends in Pakistan. It highlights fundamental issues related to rural poverty and offers key approaches to enhancing agricultural productivity for food security and poverty alleviation in rural Pakistan.